Mucocutaneous presentations of consultant critical and non-critical cases of admitted COVID-19 patients, outpatients, and vaccine-associated dermatoses: a clinical atlas and a large original study of two general COVID-19 centers from Iran - Sadeghzadeh-Bazargan, Afsaneh; Goodarzi, Azadeh (Dermatology Reports, 2023)
Rapid and proper diagnosis of mucocutaneous presentations of COVID-19 which in many cases are representing internal organ damage is a key way to better approach these patients, and it could be even lifesaving. In this original study, we reported consultant critical and non-critical cases of admitted COVID-19 patients and some interesting outpatient cases for 14 months, and some newly encountered vaccine-associated dermatoses. We presented 121 cases divided into 12 categories; all had full multi-aspects photographs attached as an atlas to a Supplementary File. These categories were:1- Generalized papulopustular eruptions (3 patients), 2- Erythroderma (4 patients), 3- Maculopapular lesions(16 patients), 4- Mucosal lesions (8 patients), 5- Urticarial lesions and angioedema (16 patients), 6- Vascular injuries (22 patients), 7- Vesiculobullous lesions (12 patients), 8- The specific new onset of mucocutaneous presentations or aggravation of any especial previous dermatoses (9 patients), 9- Nail changes (3 patients), 10- Hair loss (2 patients), 11- Non-specific mucocutaneous problems (16 patients) and 12-Vaccine-associated dermatoses (10 patients).In the pandemic, if we countered with extensive mucocutaneous lesions with vascular components or vesiculobullous erosive lesions in association with any cutaneous rash that could be an alarming sign of a probable life-threatening systemic event, we would need to approach them as soon as possible.